Analysis Endurance Profile (Vo2max) of Women's Volleyball Athletes: Yo-yo intermittent test level 1 - Rubiyatno; Eka Supriatna; Didi Suryadi; Mimi Haetami; Ghana Firsta Yosika (Indonesian Journal of Physical Education and Sport Science)
Study objectives . VO2max endurance is needed in volleyball, because this sport has the characteristics of jumping and shifting in various directions quickly. This study aims to determine endurance (VO2max) in female volleyball athletes at the Brojomusti club.